Analysis of the Students' Persuasive Paragraph Writing Ability at University - Juwita Crestiani M; Opik Dwi Indah; Hermini Hermini (Institut Agama Islam Negeri Palopo, 2022)
This research deals with analysis of the students' persuasive paragraph writing ability at the third semester of Palopo cokroaminoto university. The population of this research is the third semester students of Primary School Teacher Education Study Program of Palopo Cokroaminoto University in academic year 2022/2023. The total number of population was 200 students. The researcher applied the purposive sampling technique and there are 35 students as sample. Writing test is the instrument of this research. Based on the findings and discussion in the previous chapter, the researcher concludes analysis of the students' persuasive paragraph writing ability at the third semester of Palopo cokroaminoto university was good classification by the mean score in value range 75-87. It can be supported by the students’ content mean score was 83.66. The students’ organization mean score was 81.83. The students’ vocabulary mean score was 81.83. The students’ language use mean score was 81.06. The students’ mechanics mean score was 80.00. Therefore, analysis of the students' persuasive paragraph writing ability at the third semester of Palopo cokroaminoto university was good classification